Upaya Meningkatkan Kemampuan Siswa dalam Pengenalan Huruf Hijaiyah melalui Media Flash Card pada Siswa Kelas SDN 19 Ujuang Guguak - Ayu Vadilla; Aldi Sapri; Sanja Trihardi; Dini Fitri Milenia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to improve students' understanding of the Hijaiyah alphabet through the use of flash cards in the first grade of 19 Ujuang Guguak for the 2023–2024 academic year. This study uses the Classroom Action Research (CAR) approach based, conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The research subjects are all 31 first-grade students. The instruments used include observation sheets, lesson plan assessment sheets, and learning outcome tests in the form of pre-tests and post-tests. The results of the study indicate that the use of flash cards is effective in improving students' understanding of the Hijaiyah alphabet. This is evident from the increase in the number of students who achieved learning mastery from 32% (10 students) in the pre-cycle, increasing to 55% (17 students) in cycle I, and reaching 87% (27 students) in cycle II. The conclusion of this study is that the use of flash cards can enhance students' understanding of the Arabic alphabet. Additionally, this medium can boost students' motivation and enthusiasm for learning, making the learning process more engaging and interactive.